An Analysis of Vocabulary Mastery of Grade IX Students in Narrative Texts at SMP Negeri 1 Siantar - Juliana Tifani; Selviana Napitupulu (Educate : Journal of Education and Learning, 2026)
This study aims to analyze the vocabulary mastery of ninth-grade students in narrative texts at SMP Negeri 1 Siantar. Vocabulary plays a crucial role in supporting students’ language skills; however, many learners still experience difficulties in using vocabulary appropriately in narrative contexts. This research employed a descriptive quantitative design involving 30 students of class IX-6. Data were collected through a 40-item multiple-choice vocabulary test covering four aspects: verb word class, noun meaning, adjective use, and word collocation. The results indicated that the students’ mean score was 72.4, categorized as fair. Students performed best in noun meaning (76%), followed by adjective use (70%) and verb word class (68%), while word collocation showed the lowest achievement (65%). These findings suggest that students possess relatively adequate receptive vocabulary knowledge but face challenges in applying vocabulary contextually in narrative texts. The study contributes to EFL vocabulary research by providing a diagnostic profile of learners’ vocabulary strengths and weaknesses in narrative text comprehension, which can inform more effective vocabulary instruction. Therefore, it is recommended that English teachers implement contextual and communicative vocabulary teaching strategies, such as storytelling and retelling activities, to enhance students’ productive vocabulary use.